2022
DOI: 10.1007/s10570-021-04391-8
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced curcumin loaded nanocellulose: a possible inhalable nanotherapeutic to treat COVID-19

Abstract: Graphical abstract Nanocellulose/polyvinyl alcohol/curcumin (CNC/PVA/curcumin) nanoparticles with enhanced drug loading properties were developed by the dispersion of nanocellulose in curcumin/polyvinyl alcohol aqueous medium. Due to the physical and chemical nature of sulphuric acid hydrolyzed nanocellulose and the antiviral properties of curcumin, the possibility of using these nanoparticles as an inhalable nanotherapeutic for the treatment of coronavirus disease 2019 (COVID-19) is discussed. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 101 publications
0
25
0
Order By: Relevance
“… 59 The enhancement of curcumin's solubility will significantly improve drug loading in nanocellulose, and this curcumin presents a promising nano‐based approach for treating COVID‐19. 60 Silymarin, extracted from milk thistle, has a protective effect during lung injury because of its ability to decrease the production of nitric oxide and the infiltration of inflammatory cells. 61 Additionally, silymarin has recently been considered a potent inhibitor for ACE2, preventing its host‐cell entry.…”
Section: Effect Of Curcumin On Treating Covid ‐19mentioning
confidence: 99%
“… 59 The enhancement of curcumin's solubility will significantly improve drug loading in nanocellulose, and this curcumin presents a promising nano‐based approach for treating COVID‐19. 60 Silymarin, extracted from milk thistle, has a protective effect during lung injury because of its ability to decrease the production of nitric oxide and the infiltration of inflammatory cells. 61 Additionally, silymarin has recently been considered a potent inhibitor for ACE2, preventing its host‐cell entry.…”
Section: Effect Of Curcumin On Treating Covid ‐19mentioning
confidence: 99%
“…Nanocellulose/polyvinyl alcohol/curcumin (CNC/PVA/curcumin) NPs were produced as a nanotechnology treatment method with increased medicine loading for intranasal injection of antiviral agents SARS-CoV-2 infection. The results showed that the increased loading of curcumin in nanocellulose will supply an encouraging NPs-based solution for the therapy of SARS-CoV-2 infection [ 74 ]. In other studies, nano entrapped polyphenolic compounds were developed as a therapeutic agent against COVID-19.…”
Section: Application Of Different Nanoparticles Against Viral Infectionsmentioning
confidence: 99%
“…Notably, curcumin‐loaded CNCs were proposed as a possible inhalable nano‐therapeutic for the treatment of the prevailing coronavirus disease 2019 (COVID‐19) due to its potential inhibitory effects on the positively charged glycoproteins of the severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) virus. [ 144 ]…”
Section: Biomedical Applications Of Nanocellulosementioning
confidence: 99%